If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 2(6) + b Multiply 2 * 6 3 = 12 + b Solving 3 = 12 + b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. 3 + -1b = 12 + b + -1b Combine like terms: b + -1b = 0 3 + -1b = 12 + 0 3 + -1b = 12 Add '-3' to each side of the equation. 3 + -3 + -1b = 12 + -3 Combine like terms: 3 + -3 = 0 0 + -1b = 12 + -3 -1b = 12 + -3 Combine like terms: 12 + -3 = 9 -1b = 9 Divide each side by '-1'. b = -9 Simplifying b = -9
| 221.9352=19.468*w | | x^2+8x+16=-1 | | 6x^4-30x^2+20=0 | | 8(X-2)=72 | | 0=-3x-2y-5 | | 18*18=6x*24x | | 8=92-8x | | 8-e=e | | 6+15y=39 | | (x-1)(x+2)=2(x-4)(x+4) | | 3x+9=3x-8 | | 13+g=31 | | 2p-3r=7 | | 5c=24-c | | t+15=27 | | 64-8x=4x+4 | | 3a+10+5a=-35 | | 4(8-5y)=-2y-4 | | 9x+4=-7 | | 7x+70=14 | | 6x-27=1.8 | | 4=2*3 | | 282.286=2*30.1754+L | | Y=3.5+46 | | 10=(x-2)+2 | | 19u+v-6u+4v= | | f(2)=7*2-5 | | 2(3n-4)=34 | | 2.3=4 | | 0.20+0.60(400)=0.30(400+x) | | 4n+1=37 | | b^2=-15b-56 |